The Effect of Servant Leadership, and Psychological Empowerment on Organizational Citizenship Behavior Through Job Satisfaction as a Mediator - Misthika Dewi; Kusuma Chandra Kirana; Syamsul Hadi (Jurnal Manajemen (Edisi Elektronik), 2025)
Human resources (HR) are the key to organizational success, where organizational citizenship behavior is influenced by servant leadership, psychological empowerment, and job satisfaction. This study aims to analyze the influence of servant leadership and psychological empowerment on organizational citizenship behavior (OCB) with job satisfaction as a mediating variable at PT Metrocom Global Solusi. A quantitative approach was used with a saturated sample technique, involving the entire population of 133 employees as respondents. Data were collected through questionnaires and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results indicate a positive and significant effect of servant leadership on OCB and job satisfaction. Psychological empowerment shows a positive and significant influence on job satisfaction and OCB. Job satisfaction demonstrates a positive and significant effect on OCB. Job satisfaction can act as a mediating variable between servant leadership and psychological empowerment toward OCB. The implications of these findings are the importance of implementing servant leadership and psychological empowerment in organizations to enhance job satisfaction, which in turn promotes the growth of OCB as a positive contribution of employees toward achieving organizational goals.